Factors Affecting the Length of Hospital Stay in Hypercapnic Respiratory Failure - Maşide Ari; Tarkan Ozdemir; Murat Yildiz; Deniz Celik; Eren Usul; Emrah Ari; Ömer Faruk Tüten (Diagnostics)
Background/Objectives: Hypercapnic respiratory failure (HRF) is a primary cause of admittance to the intensive care unit (ICU). This study aimed to investigate the factors that affect the length of hospital stay in HRF patients. Methods: This study was designed as a retrospective, cross-sectional analysis of patients who were admitted to the ICU because of HRF between 2022 and 2024. The demographic and clinical characteristics of the patients and laboratory results were recorded. The Charlson Comorbidity Index (CCI) was calculated. The relationship between these parameters and the length of hospital stay was assessed. Results: A total of 138 patients were included in the study. The average length of hospital stay was 11.45 days, and 37% of the patients were included in the long-term hospitalization group. The degree of hypercapnia was not associated with the length of hospital stay. It was determined that the patients’ albumin levels and CCI were significant determinants of the length of hospital stay. The combined assessment of these two parameters was found to be superior compared to their separate evaluations. Conclusions: In our study, hypoalbuminemia and a higher CCI were identified as predictors of a prolonged ICU stay in HRF patients. Albumin levels of <3.25 g/dL and CCI scores of ≥5 were linked to longer stays, with this combined evaluation offering greater predictive value. These factors can guide patient management.